2019
DOI: 10.4070/kcj.2019.0194
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Guideline for Cardiac Rehabilitation in Korea: Recommendations for Cardiac Rehabilitation and Secondary Prevention after Acute Coronary Syndrome

Abstract: Though clinical practice guidelines (CPGs) for cardiac rehabilitation (CR) are an effective and widely used treatment method worldwide, they are as yet not widely accepted in Korea. Given that cardiovascular (CV) disease is the second leading cause of death in Korea, it is urgent that CR programs be developed. In 2008, the Government of Korea implemented CR programs at 11 university hospitals as part of its Regional Cardio-Cerebrovascular Center Project, and 3 additional medical facilities will be added in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 165 publications
(157 reference statements)
0
46
0
2
Order By: Relevance
“…Therefore, even with a low number of adverse events, it is not possible to observe the magnitude of response of these variables. It is important to highlight that in exercise programs for cardiac rehabilitation, recommended intensity ranges varying between 40% and 85% of the reserve heart rate (Kim et al, 2019); thus, the intensity range of the present study denotes less cardiovascular overload during its execution, meeting the recommendations of Kim et al (2019). Even Powell et al (2018) indicated no advantages, neither in relation to mortality nor in the number of hospitalizations for patients after cardiocirculatory events that included physical exercises in their rehabilitation routine when compared to those that did not.…”
Section: Discussionmentioning
confidence: 60%
“…Therefore, even with a low number of adverse events, it is not possible to observe the magnitude of response of these variables. It is important to highlight that in exercise programs for cardiac rehabilitation, recommended intensity ranges varying between 40% and 85% of the reserve heart rate (Kim et al, 2019); thus, the intensity range of the present study denotes less cardiovascular overload during its execution, meeting the recommendations of Kim et al (2019). Even Powell et al (2018) indicated no advantages, neither in relation to mortality nor in the number of hospitalizations for patients after cardiocirculatory events that included physical exercises in their rehabilitation routine when compared to those that did not.…”
Section: Discussionmentioning
confidence: 60%
“…Ideally, these centers should serve as vertical institutions that provide services ranging from acute care to health promotion and rehabilitation. 46) To eliminate or minimize the disparities in acute care and case fatalities between rural and urban areas, expansion of regional CCVCs and establishment of new local CCVCs are highly recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients with OPCABG can avoid injury to themselves under nonphysiological conditions while undergoing surgical treatment. 18 The effect of OPCABG on the coagulation system causing hypercoagulability must be considered. APE is a serious complication in patients with OPCABG.…”
Section: Discussionmentioning
confidence: 99%